Karakterisasi Conducted Emission Noise pada Inverter di Sistem Photovoltaic Off-Grid - Yudhistira; Dwi Mandaris; Yoppy; Hutomo Wahyu Nugroho; Prayoga Bakti; Bayu Utomo; Tyas Ari Wahyu; Siddiq Wahyu Hidayat; Ferdaus Ario Nurman; Tri Desmana Rachmilda; Deny Hamdani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The conducted emission noise caused by the inverter in the off-grid photovoltaic (PV) system has been characterized. Noise that propagates in the conduction path was generated from the phenomenon of inverter switching for the power conversion process from direct current (DC) to alternating current (AC). The IEC 62920: 2017 and CISPR 25: 2016 standards were used to measure the noise generated by the inverter on the DC side. The conducted emission noise measurements for the inverter were carried out in three conditions, namely no-load condition, connected to a 60 W incandescent lamp load, and connected to the incandescent lamp load and dimmer for power variation. Measurements were made on five inverters with different power capacities and output types. The 200 W, 300 W, and 700 W outputs were for the modified sine wave output voltage, while the 500 W and 1,000 W were for pure sine wave output voltage. The measurement results show that when the inverter is connected to the load of the incandescent lamp and the dimmer, the 500 W and 1,000 W pure sine wave inverters have a low peak noise level and less potential to cause electromagnetic interference on the DC side.